Chemoradiotherapy using retrograde superselective intra-arterial infusion for tongue cancer: Analysis of therapeutic results in 118 cases. (April 2018) - Mitsudo, Kenji; Hayashi, Yuichiro; Minamiyama, Shuhei; Ohashi, Nobuhide; Iida, Masaki; Iwai, Toshinori; Oguri, Senri; Koizumi, Toshiyuki; Kioi, Mitomu; Hirota, Makoto; Koike, Izumi; Hata, Masaharu; et al.
Highlights: 118 patients with squamous cell carcinoma of the tongue were treated with retrograde intra-arterial chemoradiotherapy. Three-year locoregional control and overall survival rates were 80.3% and 81.5%, respectively. Intra-arterial chemoradiotherapy might be an initial definitive treatment for patients with tongue cancer. Abstract: Objectives: To evaluate the therapeutic results and rate of organ preservation in patients with squamous cell carcinoma of the tongue treated with retrograde superselective intra-arterial chemoradiotherapy. Materials and methods: Between June 2006 and June 2015, 118 patients with tongue cancer were treated with intra-arterial chemoradiotherapy. Treatment consisted of radiotherapy (total 50–70 Gy) and daily concurrent intra-arterial chemotherapy (docetaxel, total 50–70 mg/m 2 ; cisplatin, total 125–175 mg/m 2 ) for 5–7 weeks. Locoregional control and overall survival rates were calculated by the Kaplan-Meier method. Cox's proportional hazards model was used for both univariate and multivariate analyses. Results: The median follow-up for all patients was 38.5 months (range, 3–129 months). After intra-arterial chemoradiotherapy, primary site complete response was achieved in 113 (95.8%) of 118 cases. Three-year locoregional control and overall survival rates were 80.3% and 81.5%, respectively. Grade 3 or 4 toxicities included neutropenia in 16.1% and mucositis in 87.3%. Grade 3 toxicities included anemia in 12.7%, thrombocytopenia in 3.4%, nausea/vomiting in 3.4%, dermatitis in 45.7%, dysphagia in 74.6%, and fever in 2.5% of patients. Late toxicity consisting of grade 3 osteoradionecrosis of the jaw occurred in 4.2% of patients. On univariate analysis, T stage and overall stage were significantly associated with locoregional control, and N stage and overall stage were significantly associated with overall survival. On multivariate analysis, the only significant predictor of overall survival was overall stage classification. Conclusion: Retrograde superselective intra-arterial chemoradiotherapy for tongue cancer provided good overall survival and locoregional control.